2014
DOI: 10.1093/nar/gku1337
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated mutations in a conserved structural motif alter physical and biochemical properties of human RAD51 recombinase

Abstract: Human RAD51 protein catalyzes DNA pairing and strand exchange reactions that are central to homologous recombination and homology-directed DNA repair. Successful recombination/repair requires the formation of a presynaptic filament of RAD51 on ssDNA. Mutations in BRCA2 and other proteins that control RAD51 activity are associated with human cancer. Here we describe a set of mutations associated with human breast tumors that occur in a common structural motif of RAD51. Tumor-associated D149N, R150Q and G151D mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 40 publications
4
48
0
1
Order By: Relevance
“…Fragment 1 (T1) is the N-terminal domain of RAD51, containing residues 86 and 89, which are essential for RAD51 homo-oligomerization and filament formation (31). Fragment T2 contains the Walker motifs essential for ATP-binding and nucleotide-binding (32). Fragment T3 contains the BRCA2-binding domain (30) and fragment T4 is the C-terminus of RAD51.…”
Section: Resultsmentioning
confidence: 99%
“…Fragment 1 (T1) is the N-terminal domain of RAD51, containing residues 86 and 89, which are essential for RAD51 homo-oligomerization and filament formation (31). Fragment T2 contains the Walker motifs essential for ATP-binding and nucleotide-binding (32). Fragment T3 contains the BRCA2-binding domain (30) and fragment T4 is the C-terminus of RAD51.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies identified three breast cancer-associated RAD51 missense mutations, the somatic variants D149N and G151D, and the germline variant R150Q (1921). These mutations, from different individuals, occurred in adjacent residues of a conserved Schellman loop motif that occupies a prominent position on the outer surface of the RAD51 presynaptic filament (20). The motif is distant from binding sites for DNA, ATP, BRCA2 and PALB2, but it is near a reported p53 binding site (2325).…”
Section: Introductionmentioning
confidence: 99%
“…The motif is distant from binding sites for DNA, ATP, BRCA2 and PALB2, but it is near a reported p53 binding site (2325). All three RAD51 mutants are proficient in DNA pairing and strand exchange, but they form presynaptic filaments with altered physical and biochemical properties (20). The R150Q and G151D variants have low catalytic efficiencies for ssDNA-stimulated ATP hydrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…1C) the greatest similarity in the central and carboxyl terminal regions, but their N-terminal regions were less well aligned. Interestingly, GdDMC1A has an extended amino terminal region and lacks the recently described Schellman loop [30] (Fig. 1B), while GdDMC1B conserves this motif.…”
Section: Gddmc1a and Gddmc1b Possess Conserved Recombinase Domainsmentioning
confidence: 67%
“…The specific functions of each GdDMC1 might depend on the possible interactions in this region. In addition to the conventional motifs identified in giardial recombinases, a new motif was recently identified: the Schellman loop [30]. The Schellman loop seems to be conserved among Rad51 proteins from different species, and it could assist in interactions with solvents, ions or protein partners.…”
Section: Discussionmentioning
confidence: 99%